Peripherally inserted central catheters versus implantable port catheters for cancer patients: a meta-analysis - Lin, Li; Li, Wei; Chen, Chen; Wei, Anhua; Liu, Yu (Frontiers in Oncology, 2023)
Background The implanted vascular access ports (PORTs) were compared with peripherally inserted central catheters (PICCs) as the administration of chemotherapy regarding different clinical effects and adverse effects. Which is better is debatable. Hence, the current study was conducted to assess the safety and efficacy of these two optimal vascular access strategies. Methods The following electronic databases were searched: PubMed, Embase, and the Cochrane Library updated in May 2023. Studies on the differences in complication rates in patients with cancer using either PICC or PORT for chemotherapy were included. Meta-analysis Revman 5.3 software was used for statistical analysis. Results A total of 22 articles were retrieved. The results suggested that PORT has a superior safety profile, with lower incidences of overall adverse effects (OR=2.72, 95% CI=1.56–4.72 P=0.0004), catheter-related thrombosis (OR=2.84, 95% CI=1.97–4.11, P<0.00001), and allergic reactions (OR=6.26, 95% CI=1.86–21.09, P=0.003) than typically expected with PICC. Moreover, PICC was non-inferior to the PORT group with respect to DVT (OR=2.00, 95% CI=0.86–4.65, P=0.11) and infection (OR=1.55, 95% CI=0.75–3.22, P=0.24). Conclusion PORT achieved safety benefits compared with chemotherapy through PICC. Therefore, PORT is regarded as safe and effective vascular access for the administration of chemotherapy. When considering economic factors and some key elements, more high-quality research would help verify these clinical benefits. Systematic review registration https://www.crd.york.ac.uk/prospero/, identififier CRD42023421690.